CHATBOTS AND CUSTOMER SERVICE SATISFACTION - Shendge, Dr. Rajashri Abhijit (The journal of contemporary issues in business and government, 2022)
Most of the businesses are using chatbots on their website to improve customer service performance. Today’s customer wants to spend less time overall, thus they want to be able to contact businesses anytime, anywhere, and through any channel. This study sheds light on how chatbots affect a company's ability to improve customer service performance and retain customers. To provide a positive customer experience, a chatbot must adhere to critical criteria in the areas of system quality, service quality, and information quality. Companies can change the language style of a chatbot to make it more personable. Customers are more satisfied and trusting of chatbots when they resemble humans, which increases chatbot adoption.